DETEKSI BUKU PERPUSTAKAAN FAKULTAS DENGAN APLIKASI RFID BERBASIS WEB - Chandrawati, T. Brenda; Farrid Christanti, Risa Farrid; Sanjaya, Ridwan (PROXIES, 2012)
RFID is an identification technology that can be used in various applications, one of which is the detection of books in the library. It aims to facilitate the transaction. Developmeuat conducted in the use of RFID is the detection of the presence of books in the library that utilizes a web application with a local server. Keyword: identification technology, detection, web application